Perilaku Dunia Usaha dalam Melakukan Adopsi Inovasi Pertanian - Nurjaman Nurjaman; Ujang Sumarwan; Kirbrandoko Kirbrandoko (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2015)
This research was conducted to analyze the effect of attitude toward the behavior, subjective norms, and perceived behavioral control on the intention to adopt the business world in agriculture. This research was important to look at the behavior of the business world in adopting agricultural innovations that will increase the amount of innovation that will be adopted by the businesspeople. This research was uses the theory of planned behavior developed by Ajzen. This research was conducted directly to businesses spread in Jakarta, Bogor, Bandung, Semarang, Surabaya, Malang and Borneo during February to April 2014. Research data was obtained by conducting interviews to businesses by using a questionnaire. The sample of respondents used in this study is the population of the world crop of technology businesses that have done or have followed the adoption of innovation promotion activities of IAARD. The variables used in this study was the effect of attitude toward the behavior, subjective norms, and perceived behavioral control as independent variables in the business world and the intention to adopt innovation as the dependent variable. Data were analyzed using multiple regression analysis tool Minitab 16 and also performed a descriptive analysis. The results showed that the intention of doing business in the innovation adoption is significantly affected by the components of attitude toward the behavior, subjective norms, and behavioral control. From this study can be applied to marketing strategies to increase the amount of innovation is the adoption of more intensive cooperation with relevant institutions in marketing activities that the institution will provide advice in making innovation to the world of business. From this research further research could be developed in the form of other components that may affect the business community in adopting agricultural innovations.